Finland's Strategic Shift: A New Chapter with NATO Membership - Akbar, Yonarisman Muhammad; fadiyah, dina (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
This paper delves into Finland's potential accession to NATO, marking a significant departure from its longstanding policy of military non-alignment. As geopolitical dynamics in the Baltic region undergo profound changes, Finland's consideration of NATO membership carries far-reaching implications for regional security and global geopolitics. Finland responded to Russian aggressiveness by joining the North Atlantic Treaty Organization (NATO) to counteract Russia’s security threats in the region. The abstract explores the historical context of Finland's neutrality, the evolving security landscape, and the factors driving the nation towards reevaluating its defense posture. Using the research method of critical content analysis and in-depth interview with military and defense and security analyst Rahakundini, the potential impact on NATO, Russia's response, and the broader implications for the delicate balance of power in Northern Europe. The proposed NATO membership signals a strategic recalibration for Finland, with ramifications extending beyond national borders, shaping the geopolitical narrative in an ever-evolving international arena.